2023
DOI: 10.3389/fimmu.2022.1076883
|View full text |Cite
|
Sign up to set email alerts
|

Advances in artificial intelligence to predict cancer immunotherapy efficacy

Abstract: Tumor immunotherapy, particularly the use of immune checkpoint inhibitors, has yielded impressive clinical benefits. Therefore, it is critical to accurately screen individuals for immunotherapy sensitivity and forecast its efficacy. With the application of artificial intelligence (AI) in the medical field in recent years, an increasing number of studies have indicated that the efficacy of immunotherapy can be better anticipated with the help of AI technology to reach precision medicine. This article focuses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…They effectively coordinate autocrine and paracrine functions by transmitting mRNAs, miRNAs, lncRNAs and tsRNAs, thereby modulating the tumour microenvironment and facilitating tumour cell growth and metastasis. 29 , 30 Given the observed increase in mRNA levels of PDE4C in OS cells co‐cultured with M2 macrophages, we hypothesized that the transfer of PDE4C from M2 macrophages to OS cells is reliant on an mRNA delivery mechanism, such as exosome. In accordance with our hypothesis, the presence of PDE4C mRNA was observed in exosomes derived from M2 macrophages, while no protein was detected.…”
Section: Discussionmentioning
confidence: 99%
“…They effectively coordinate autocrine and paracrine functions by transmitting mRNAs, miRNAs, lncRNAs and tsRNAs, thereby modulating the tumour microenvironment and facilitating tumour cell growth and metastasis. 29 , 30 Given the observed increase in mRNA levels of PDE4C in OS cells co‐cultured with M2 macrophages, we hypothesized that the transfer of PDE4C from M2 macrophages to OS cells is reliant on an mRNA delivery mechanism, such as exosome. In accordance with our hypothesis, the presence of PDE4C mRNA was observed in exosomes derived from M2 macrophages, while no protein was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by the latest advancement in artificial intelligence, we traversed 20 mainstream machine learning algorithms to fit the data and improve performance ( Wolpert and Macready, 1997 ; Xie et al, 2023 ). We found that Extra Tree had the highest predictive performance.…”
Section: Discussionmentioning
confidence: 99%
“…The TME not only plays a major role in tumor progression, but also orchestrates immune components, thus affecting the therapeutic efficacy of ICB and patient prognosis (44,45). Recent research suggests that epigenetic changes, usually caused by chronic inflammation, occur in cancer cells and other TME components (46,47).…”
Section: Discussionmentioning
confidence: 99%